CONJUGATED LINOLEIC ACID, FATTY ACID PROFILE AND PROCESS PROPERTIES IN KUMIS - FERMENTED MILK CONSUMED IN COLOMBIA - OSORIO, Julián A.; RAMÍREZ, Carloina; NOVOA, Carlos F.; GUTIÉRREZ, Luis-Felipe (Vitae, 2011)
In this study, we reported the concentration of conjugated linoleic acid of the main commercial kumis consumed and distributed in Colombia, as well as the concentration of conjugated linoleic acid of an artisanal kumis elaborated with two different types of milk (skim liquid and powder reconstituted). Conjugated linoleic acid (C18:2c9t11) contents, expressed as mg of rumenic acid/g fat, ranged from 7.63 ± 0.96 to 22.62 ± 3.85. Also, the main fatty acids of kumis samples were identified and quantified. pH value ranged between 3.84 ± 0.02 and 4.28 ± 0.01, and titratable acidity ranged between 0.69 ± 0.01 and 0.94 ± 0.02% of lactic acid. Consistence and flux indices presented values between 2.01 ± 0.05 and 7.08 ± 0.39 (Pa·sn) and from 0.43 to 0.26, respectively. These results indicate that kumis is a food product that could be used for supplying important amounts of conjugated linoleic acid in the human diet.